Preliminary Assessment of Utilizing Wood Sawdust as Pore Forming Agent in Porous Ceramic - Md Zulkifli, Muhammad Luqman Hakim (2020)
The porous ceramic is mainly used as insulator, and highly applicable in ceramic tile and construction purposes. There is small amount of researcher that applying the natural pore forming agent to create the porous ceramic due the particle size and pore distribution that inconsistence. Thus, this research is conducted to utilize the potential of wood sawdust as pore forming agent in porous ceramic, then to investigate the effects of wood sawdust content weight percentage (wt. %) and firing temperature to physical and mechanical properties of porous ceramic thermal insulator. There are two compositions that created by using the china clay and wood sawdust, which are 10 wt. % and 20 wt. % of wood sawdust. The wood sawdust is sieved for 300 μm to make sure the consistent size of wood sawdust is achieved. Then the mixing of clay and sawdust is proceeded with drying process for 110oC and firing process for 900oC to get the expected mechanical strength. The porous ceramic is inspect under several characterizations to inspect the mechanical and physical properties of porous ceramic. The characterization including the Fourier Transform Infrared (FTIR) to show the wavenumber and it proved the by-product is a wood, then the Optical Microscope (OM) is used to check the morphology of the porous ceramic that mainly tend to become highly porosity that influenced by the by-product that added into to composition, then the water absorption is conducted to measure the apparent porosity, bulk density and water absorption. It is show that water absorption affect the mechanical strength of porous ceramic. The compression test is conducted for the inspection of mechanical strength (compressive strength), the result show that compressive strength decreases as the composition of the waste wood sawdust increases as the porosity of the ceramic lead to lower density. The increases of the water absorption value, it reduce the density due to the porosity hence the mechanical strength decreases.